Graphene Oxide: Microscopic Evidence for Strong Interaction between Pd and Graphene Oxide that Results in Metal‐Decoration‐Induced Reduction of Graphene Oxide (Adv. Mater. 15/2017). Issue 15 (April 2017) - Jeon, Jong‐Myeong; Kim, Taemin Ludvic; Shim, Young‐Seok; Choi, You Rim; Choi, Seokhoon; Lee, Seonyong; Kwon, Ki Chang; Hong, Seong‐Hyeon; Kim, Young‐Woon; Kim, Soo Young; Kim, Miyoung; Jang, Ho Won
Abstract : The strong interaction between Pd and graphene oxide leads to the formation of a PdO interlayer between graphene oxide and a Pd nanoparticle, which results in the absorption of oxygen functional groups of GO. As described by Miyoung Kim, Ho Won Jang, and co‐workers in article number 1605929, the PdO interlayer diminishes the lattice mismatch between the Pd nanoparticles and the GO, which imparts a pseudo‐epitaxial relationship to the Pd and the GO.